2020
DOI: 10.5194/acp-20-8381-2020
|View full text |Cite
|
Sign up to set email alerts
|

Fast responses on pre-industrial climate from present-day aerosols in a CMIP6 multi-model study

Abstract: Abstract. In this work, we use Coupled Model Intercomparison Project Phase 6 (CMIP6) simulations from 10 Earth system models (ESMs) and general circulation models (GCMs) to study the fast climate responses on pre-industrial climate, due to present-day aerosols. All models carried out two sets of simulations: a control experiment with all forcings set to the year 1850 and a perturbation experiment with all forcings identical to the control, except for aerosols with precursor emissions set to the year 2014. In r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 94 publications
2
29
0
Order By: Relevance
“…Furthermore, studies show that the hemispheric contrast in aerosol forcing has shifted the tropical rainbelt southward, which is associated with a weakening of the west African monsoon and the occurrence of the Sahel drought of the mid-1980s (Rotstayn and Lohmann, 2002;Biasutti and Giannini, 2006;Allen and Sherwood, 2011;Ackerley et al, 2011;Chang et al, 2011;Biasutti, 2013;Hwang et al, 2013;Dong et al, 2014;Allen et al, 2015;Undorf et al, 2018). The observed precipitation decrease during recent decades over most of the areas affected by the south and east Asian monsoon can also be explained by the dominance of aerosol radiative effects suppressing precipitation over the expected precipitation enhancement due to increased GHGs (Wang et al, 2013;Song et al, 2014;Li et al, 2015;Xie et al, 2016;Krishnan et al, 2016;Guo et al, 2016;Lau and Kim, 2017;Zhang et al, 2017;Lin et al, 2018;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, studies show that the hemispheric contrast in aerosol forcing has shifted the tropical rainbelt southward, which is associated with a weakening of the west African monsoon and the occurrence of the Sahel drought of the mid-1980s (Rotstayn and Lohmann, 2002;Biasutti and Giannini, 2006;Allen and Sherwood, 2011;Ackerley et al, 2011;Chang et al, 2011;Biasutti, 2013;Hwang et al, 2013;Dong et al, 2014;Allen et al, 2015;Undorf et al, 2018). The observed precipitation decrease during recent decades over most of the areas affected by the south and east Asian monsoon can also be explained by the dominance of aerosol radiative effects suppressing precipitation over the expected precipitation enhancement due to increased GHGs (Wang et al, 2013;Song et al, 2014;Li et al, 2015;Xie et al, 2016;Krishnan et al, 2016;Guo et al, 2016;Lau and Kim, 2017;Zhang et al, 2017;Lin et al, 2018;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Tropical regions, which also tend to have the greatest societal vulnerability to precipitation disruption, are the most susceptible to dynamically-driven precipitation changes generated by both local and remote aerosol emissions, as has been highlighted elsewhere (e.g. Scannell et al, 2019;Westervelt et al, 2018;Zanis et al, 2020). However, these regions are also for the precipitation stability of vulnerable regions outside of key past or projected emissions hotspots.…”
Section: Discussionmentioning
confidence: 91%
“…Future aerosol emissions reductions could greatly aggravate the warming effect caused by greenhouse gas (GHG) forcing (Lin et al, 2016;Hienola et al, 2018), particularly in eastern and southern Asia, and may increase surface temperatures by 0.5°C in some regions (Westervelt et al, 2015;Chuwah et al, 2016) and cause a significant increase in extreme high-temperature events (Wang et al, 2016;Samset et al, 2018;Luo et al, 2020). Future aerosol reductions may also shift the tropical rain belt northwards, enhancing precipitation in the Asian monsoon region (Westervelt et al, 2018;Zanis et al, 2020) and shifting both the mean and extreme values of precipitation toward larger values (Zhao et al, 2018). Asia is a region where extreme precipitation is particularly sensitive to aerosol reductions (Lin et al, 2016;Samset et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies in this field have been conducted to date. A recent study considering emissions reductions of aerosols, ozone, and their precursors showed that future non-methane SLCF reductions will not only improve air quality but also increase global mean temperature, precipitation, and climate extremes in the mid-21st century, with more marked warming and wetting trends in some regions, particularly Asia and the Arctic (Allen et al, 2020). However, that study focused on trends of climate variables, and its assessment of regional climate changes, particularly climate extremes, was insufficient.…”
Section: Introductionmentioning
confidence: 99%